Smoke detection using deep Convolutional neural network - Niloy, Wahidul Hasan; Ornab, Mostafa Kamal; Saha, Saurav (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.